The first fossil record of the Emesinae genus Emesopsis Uhler (Hemiptera: Heteroptera, Reduviidae) from Eocene Baltic amber - Popov, Yuri A.; Chłond, Dominik (Zootaxa, 2015)
Two new fossil representatives of the assassin bug family Reduviidae are described as new from Baltic amber (Upper Eocene), belonging to the genus Emesopsis of the tribe Ploiariolini (Emesinae): Emesopsis putshkovi sp. nov. and E. similis sp. nov. These representatives of the Emesinae are the oldest fossil bugs of the genus Emesopsis known so far, and reported for the first time. This genus is also briefly diagnosed.